2008
DOI: 10.1002/ajmg.a.32384
|View full text |Cite
|
Sign up to set email alerts
|

Familial recurrence of SOX2 anophthalmia syndrome: Phenotypically normal mother with two affected daughters

Abstract: The SOX2 anophthalmia syndrome is emerging as a clinically recognizable disorder that has been identified in 10–15% of individuals with bilateral anophthalmia. Extra-ocular anomalies are common. The majority of SOX2 mutations identified appear to arise de novo in probands ascertained through the presence of anophthalmia or microphthalmia. In this report, we describe two sisters with bilateral anophthalmia/microphthalmia, brain anomalies and a novel heterozygous SOX2 gene single-base pair nucleotide deletion, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 11 publications
1
33
0
Order By: Relevance
“…The importance of SOX2 has been highlighted in recent literature by its involvement in reprogramming terminally differentiated cells into induced pluripotent stem cells (iPSCs) (45,64,69). Lossof-function mutations in SOX2 can cause improper eye and brain development (22,55,74,79). SOX2 downregulation in uninfected NPCs is associated with, and necessary for, both glial and neuronal differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of SOX2 has been highlighted in recent literature by its involvement in reprogramming terminally differentiated cells into induced pluripotent stem cells (iPSCs) (45,64,69). Lossof-function mutations in SOX2 can cause improper eye and brain development (22,55,74,79). SOX2 downregulation in uninfected NPCs is associated with, and necessary for, both glial and neuronal differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…21,22 The observed spectrum also includes normal eye development in heterozygote 23 and mosaic 17,[23][24][25] /queried mosaic 26 heterozygote SOX2 mutation patients, as in the mother in this case. In addition to pituitary dysfunction, a substantial proportion of SOX2 mutation patients have other cerebral abnormalities as seen in patient II.1 in this report.…”
Section: Discussionmentioning
confidence: 95%
“…17,[23][24][25][26] These mothers have all been phenotypically normal. Our case is the first report of one such mother having IHH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of the findings in this syndrome are not evident at birth. Sequencing followed by deletion studies if no mutation is identified should be considered [36,37]. In addition, parental studies and prenatal testing should be discussed with any family when a SOX2 mutation is identified.…”
Section: Key Pointsmentioning
confidence: 98%